Model Konseptual Media Pembelajaran Tech Pack untuk Mendukung Kesiapan Kerja Siswa SMK Desain dan Produksi Busana - Dya Ratna Octavianing Putri; Isnandar; Syarif Suhartadi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
The fashion industry requires vocational high school students to understand industrial work systems and production documentation in addition to sewing skills. One important document in the garment industry is the tech pack, which functions as a technical communication guide in clothing production. However, students at SMK Cendikia Bangsa still have limited understanding of the meaning, function, and preparation of a tech pack, while learning activities remain focused on garment-making practices without industry-based learning media. Therefore, this study aims to formulate a conceptual model of tech pack learning media to support the work readiness of vocational high school students in the Fashion Design and Production specialization. This study employed a literature review method with a descriptive qualitative approach. Data were collected through observation, documentation, and literature review, while data analysis used content analysis techniques. The findings resulted in a conceptual model of tech pack learning media consisting of industry needs, industry-based competencies, learning problems, learning media development, contextual learning implementation, and expected learning outcomes. The model is expected to improve students’ understanding of tech pack preparation, technical communication skills, and work readiness in the fashion industry.